2005
DOI: 10.2166/wst.2005.0587
|View full text |Cite
|
Sign up to set email alerts
|

A new modeling approach for estimating first flush metal mass loading

Abstract: The purpose of this study was to investigate pollutant mass loading from major highways in Southern California, with emphasis on interpretation of event mean concentrations and first flush effects. The results of monitoring eight sites during the 1999-2002 storm seasons found that metal contaminants had higher concentrations at the early stages of storm events compared with other stages of rain storms. A new washoff model was developed to predict the event mean concentrations of metal contaminants taking first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In a French study (Legret and Pagotto 1999), Pb was, again, found to appear mostly in the particulate form (91%), but the other metals were usually dissolved. Kim et al 2005a) also reported that most of the Pb found in runoff samples was in the particulate phase, Ni was approximately the same as in the particulate phase, while Cu and Zn were predominantly present in the dissolved phase. In a particular storm event dissolved Cu and Zn concentrations were approximately 10 and 36 times greater than in the particulate phase.…”
Section: Iron and Other Metalsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a French study (Legret and Pagotto 1999), Pb was, again, found to appear mostly in the particulate form (91%), but the other metals were usually dissolved. Kim et al 2005a) also reported that most of the Pb found in runoff samples was in the particulate phase, Ni was approximately the same as in the particulate phase, while Cu and Zn were predominantly present in the dissolved phase. In a particular storm event dissolved Cu and Zn concentrations were approximately 10 and 36 times greater than in the particulate phase.…”
Section: Iron and Other Metalsmentioning
confidence: 88%
“…The continuous input of material from traffic insures a continual increase in the cumulative constituent load throughout the duration of the storm event. Kim et al (2005a) noted that most metals exhibited first flush on concentration and mass basis. The range of metal concentrations from early stages of a storm compared to the final stages of the storm can be tenfold.…”
Section: Highway Site Situationsmentioning
confidence: 99%
“…Distinctly elevated metal levels have been reported for such runoff waters (e.g. Kim et al 2005a). The storm event on 22/1/07 (sampled in three sequential parts: #9, #10 and #11, Table 2) displayed a typical pattern of initial high intensity (as measured by runoff flow rate) followed by declining intensity during the later part of the storm.…”
Section: Road Runoff Watermentioning
confidence: 99%
“…The buildup depends on the ADD, land use, wind speed and traffic. Wash off may be a function of rainfall intensity and other factors (Kim et al 2005(Kim et al , 2006. Few researchers determined the effect of the antecedent dry period in their study of stormwater discharge (Saget et al 1996;Lee et al 2002).…”
Section: Stormwater Quality Assessment Through Modelingmentioning
confidence: 99%